Imperfect exchange rate pass-through: the role of distribution services and variable demand elasticity - Philippe Jeanfils (National Bank of Belgium, 2008)
This paper examines which mechanisms are likely to dampen the price pressures in the wake of exchange rate movements. In addition to nominal frictions frequently used in sticky-price models, it jointly introduces two features that have hitherto been considered separately in the existing literature, i.e. a variable demand elasticity à la Kimball (1995) and distribution services in the form of non-traded goods as in Corsetti and Dedola (2005). The paper explores the respective role of each feature and assesses the quantitative importance of these theoretical explanations for the exchange rate pass-through to a broad range of prices as well as for the real exchange rate and for the trade balance. Segmentation of national markets through distribution services and imperfect competition with variable mark-ups are important for accounting for the observed stability of import prices "at the border". Hence, these mechanisms help to explain the observed stability of import prices in local currency with realistic durations of price contracts.
Keywords: F3; F4; 330; exchange rate pass-through; general equilibrium; Exchange Rate Pass-Through; Inflationskonvergenz; Außenhandelspreis; Allgemeines Gleichgewicht; Theorie